Terminalia tomentosa Bark; its Commercial Potentialities - Karnik, M. G.; Bhatia, Kuldip; Lal, Jla (Indian Forester, 1970)
The studies have been made to explore the commercial potentialities of the bark of Terminalia tommtosa. The bark was analysed for Tans, Non-tans and colour of the aqueous extract. The bark was also analysed for ash, cold and hot water solubles, Alcohol/Benzeae aad pet. ether solubility, Pentosans and Lignin. The inorganic constituents of the ash of the original bark as well as that of water extracted bark were determined. Pilot plant experimeats to collect the spray dried aqueous extract were conducted and this extract was analysed for Moisture, Ash, Tans and Non-tans and the colour intensity. The laboratory experiments on the dyeing performance of the aqueous extract were carried out. The samples of this extract were also sent to (1) Indian Jute Industries Research Association, Calcutta, (2) Indequip Limited, Ahmedabad, (3) The Govt. Institute of Textile Chemistry and Knitting Technology, Ludhiana and (4) Wood Preservation Branch, F.R.I., Dehra Dun for their evaluation on dyeing performance of this extract. The extracts of their reports are reproduced in this article. The dye extract has been found suitable as a Cheap dye for dyeing cotton, wool, silk and jute fabrics. Further experiments were carried on the exhausted bark to isolate the Oxalic Acid. The Oxalic Acid of 97.2% purity in a yield of 20% could be obtained. Sample of this acid was seat to Glaxo Laboratory, Bombay who have found it suitable for their requirement. Probable industries where the bark of T. tomenlosa can be profitably utilised are indicated.